Perencanaan Perumahan Melalui Pengembangan Kawasan Permukiman di Desa Singorojo, Kecamatan Mayong, Kabupaten Jepara - Pratamaningtyas Anggraini; Intan Muning Harjanti (Jurusan Perencanaan Wilayah dan Kota, 2019)
Mayong Subdistrict is one of the sub-districts in Jepara Regency, Central Java which is designated as an industrial, trade and service area. Housing planning and housing development areas in Mayong sub-district, especially Singorojo Village, which are suitable for land use, will provide sustainable life for the community. The purpose of this study was to conduct housing planning through housing development in Singorojo Village, Mayong District, Jepara Regency. The objectives of this study are collection of topography, lithology, hydrology, climatology, geological hazards, and land use. In addition, do topographic analysis; environmental analysis; accessibility analysis; climate analysis, solar pathway, and wind direction; vegetation analysis; noise analysis; view analysis; and drainage analysis. The method used in this study uses qualitative descriptive.